2022
DOI: 10.1021/acs.jpcc.2c03367
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor and Alcohol Vapor Induced Healing of the Nanostructured KBr Surface

Abstract: Using atomic force microscopy in the pressure range of 10 –10 mbar to several tens of mbar at room temperature, we demonstrate the restructuring of nanostructured KBr surfaces assisted by the presence of water, methanol, and ethanol vapors and the formation of solvation islands. On a flat KBr surface, the two-dimensional solvation islands start nucleating at the step edges and grow with time and with increasing relative pressure. Solvation islands of water wet the terraces; however, solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In our recent study on nanostructured potassium bromide (KBr) single crystal surfaces, we showed how atomic steps could move even under lower humidity conditions. [ 44 ] We ascribed this to the ion solvation, which occurs even before the solvation layers form and wet the KBr surface. The CsPbBr 3 perovskite composition used for this study also has an ionic character and can exhibit similar solvation effects upon exposure to humidity conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study on nanostructured potassium bromide (KBr) single crystal surfaces, we showed how atomic steps could move even under lower humidity conditions. [ 44 ] We ascribed this to the ion solvation, which occurs even before the solvation layers form and wet the KBr surface. The CsPbBr 3 perovskite composition used for this study also has an ionic character and can exhibit similar solvation effects upon exposure to humidity conditions.…”
Section: Resultsmentioning
confidence: 99%